Synthesis of conducting polymers and metal nanoparticles by using ionizing radiation - Saion, Elias; Shaari, Abdul Halim; Ali, Mohammad Akbar; Hussain, Muhammad Yousuf; Mirjalili, Ghazanfar; Dahlan, K. (Malaysian Solid State Science and Technology Society (MASS), 2008)
Conducting polymer polyaniline was synthesized by radiation method from casting films contg. polyvinyl alc. (PVA) blended with aniline hydrochloride. Upon gamma -irradn. the films changed to PVA/polyaniline nanoparticles as shown by the SEM surface morphol. The UV-Visible spectrophotometer measurement revealed the absorption band of polyaniline peaking at 790 nm due to pi-pi electronic transitions of conducting polyaniline mols. (polyemeraldine based) from donor atoms (HOMO) to acceptor atoms (LUMO). The band gap decreases from 1.15 eV at 0 kGy to 1.0 eV at 50 kGy indicating the cond. of polyaniline increases with the increase of dose. Nanocomposites of PVA/Ag0 nanoparticles were synthesized under ambient condition by gamma radiation from composite of PVA/silver nitrate. The UV-vis spectroscopy revealed the absorbance peaking at 425 due to the plasmon transitions at the conduction band of Ag0 nanoparticles. The absorbance increases with dose indicating an increase of the no. of Ag0 nanoparticles formed. The absorption peak shifted from 425 nm to 415 nm corresponds to a decrease in the diam. of Ag0 nanoparticles with increasing dose. The band gap of the PVA/Ag0 nanoparticles increases with increasing dose indicating the gap of conduction band of Ag0 nanoparticles increases as the diam. of Ag0 nanoparticles decreases.